2018
DOI: 10.1016/j.compositesb.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

A micromechanical study of stress concentrations in composites

Abstract: Random and periodic representations of composite microstructures are inherently different both in terms of the resultant range of stresses that each phase carries as well as the total load over the entire volume comprising both matrix and fiber phases. In this study, an algorithm was developed to generate random representative volume elements (RVE) with varying volume fractions and minimum distances between fibers. The random microstructures were analyzed using finite element models (FEM) and the results compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(30 citation statements)
references
References 46 publications
3
27
0
Order By: Relevance
“…An acceptable size of RVE is one that is statistically representative of both the morphology and behavior of the material [26,27,28,29]. For the purpose of this study the ratio of δ = 40 was chosen, which has been shown to be representative of carbon epoxy composite materials [12,28].…”
Section: Finite Element Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…An acceptable size of RVE is one that is statistically representative of both the morphology and behavior of the material [26,27,28,29]. For the purpose of this study the ratio of δ = 40 was chosen, which has been shown to be representative of carbon epoxy composite materials [12,28].…”
Section: Finite Element Analysismentioning
confidence: 99%
“…The current study focuses on failure in the transverse direction (perpendicular to the fibres), and examines the effects of resin rich areas on failure initiation in the matrix phase. It has been shown that a realistic representation of the non-uniform distribution of fibers within the matrix of fiber-reinforced composites can have a significant impact on the magnitude and distribution of stress concentrations in finite element models of the unit cell [12]. Similarly, one could expect that this non-uniform microstructural morphology will also affect failure initiation and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Ghayoor et al. 94 investigated the influence of stress concentration and distribution in the epoxy matrix phase for the damage analysis of a composite material with random and periodic microstructure. Table 4 provides a summary of the main methodologies along with their capabilities.…”
Section: Multi-scale Computational Homogenizationmentioning
confidence: 99%
“…Praud et al 93 developed a new model accounting for anisotropic damage and an elasticity induced by microcracks in UD composite using continuum damage mechanics and RVE concept. Ghayoor et al 94 investigated the influence of stress concentration and distribution in the epoxy matrix phase for the damage analysis of a composite material with random and periodic microstructure. Table 4 provides a summary of the main methodologies along with their capabilities.…”
Section: Multi-scale Computational Homogenizationmentioning
confidence: 99%
“…However, due to the great difference in thermodynamic properties between reinforced fibers and resin matrix, the poor bonding strength at their interface makes the comprehensive properties of composites far from the expected values [2]. Stress concentration resulting from long-term use leads to serious performance degradation and short life [3].…”
Section: Introductionmentioning
confidence: 99%